2016
DOI: 10.1002/2016jc012144
|View full text |Cite
|
Sign up to set email alerts
|

Scales and dynamics of Submesoscale Coherent Vortices formed by deep convection in the northwestern Mediterranean Sea

Abstract: Since 2010, an intense effort in the collection of in situ observations has been carried out in the northwestern Mediterranean Sea thanks to gliders, profiling floats, regular cruises, and mooring lines. This integrated observing system enabled a year‐to‐year monitoring of the deep waters formation that occurred in the Gulf of Lions area during four consecutive winters (2010–2013). Vortical structures remnant of wintertime deep vertical mixing events were regularly sampled by the different observing platforms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(129 citation statements)
references
References 96 publications
(167 reference statements)
5
118
0
Order By: Relevance
“…The scale of variability associated with these changes in the upper ocean stratification (Figure a) is typically of 5–10 days and are similar to the scale of variability observed in the horizontal velocities at all levels (Figure b). This suggests an important role of submesoscale and mesoscale circulation features such as eddies during the restratification phase [ Houpert ; Bosse et al ., ]. Similar eddies were also observed in other places such as the Labrador Sea [ Lilly and Rhines ; Lilly et al ., ; Hátún et al ., ; De Jong et al ., ] or the Irminger Sea [ Fan et al ., ], where they play an important role in the restratification of the deep convection area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale of variability associated with these changes in the upper ocean stratification (Figure a) is typically of 5–10 days and are similar to the scale of variability observed in the horizontal velocities at all levels (Figure b). This suggests an important role of submesoscale and mesoscale circulation features such as eddies during the restratification phase [ Houpert ; Bosse et al ., ]. Similar eddies were also observed in other places such as the Labrador Sea [ Lilly and Rhines ; Lilly et al ., ; Hátún et al ., ; De Jong et al ., ] or the Irminger Sea [ Fan et al ., ], where they play an important role in the restratification of the deep convection area.…”
Section: Resultsmentioning
confidence: 99%
“…These SCVs induce the propagation of columnar buoyancy perturbations typically of 0.05–0.15 m 2 .s −2 as discussed in Bosse et al . []. The eddy‐induced buoyancy flux would then represent about 0.5–1.4% of the total integrated buoyancy flux over the winter (typically 1.15 m 2 .s −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The formation of cyclonic SCVs is likely favored by a winter mixed layer reaching the bottom. They are characterized by small radius (5–10 km) due to the weak stratification of the ocean deep levels and peak velocities located at great depths [ Bosse et al ., ; Damien et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…During the summer MOOSE‐GE 2012 cruise, two cyclonic SCVs were observed along the continental slope in the vicinity of the convection region [ Durrieu de Madron et al ., ; Bosse et al ., ]. The vertical profiles of density and large particle abundance in an eddy identified as a cyclonic SCV by Bosse et al .…”
Section: Discussionmentioning
confidence: 99%
“…This structure, which has also a signature in the humiclike plot (Figure 7g), is associated with a local "doming" of the isopycnals that suggests a subsurface eddy. Recent observations of submesoscale coherent vortices (SCV) that resembles the structure observed here were reported for the same geographical area (Bosse et al, 2015(Bosse et al, , 2016. However, their origins are likely different since SCV reported in these studies are observed deeper (200-500 m) and are associated with high-salinity anomalies.…”
Section: Physical-biogeochemical Interactions Across the Northern Curmentioning
confidence: 67%